PENGEMBANGAN LKPD BERBASIS DISCOVERY LEARNING BERBANTUAN CANVA PADA KELAS V SEKOLAH DASAR - Lulu Nailul Muna; Petra Kristi Mulyani (Program Studi PGSD Universitas Flores, 2023)
The problem found are that worksheet only focuses on answering question so that students' enthusiasm and activeness in learning process is low and students’ science score is low. This research aims to develop worksheet based on discovery learning assisted by Canva on heat and transfer material in 5h elementary school which will be tested for feasibility and effectiveness. This research and development uses the ADDIE research design and a true experiment design with a posttest only control design. The feasibility results by media experts are 100% (very feasible). While the feasibility by material experts is 77.3% (feasible). The effectiveness results using the independent sample t-test with a significance of 5% obtained 0.000, so that there is a significant average difference between the learning scores of the experimental class (which is 70.23) and the control class (which is 43.33). Worksheet based on discovery learning assisted by Canva on heat and displacement received a very good response from the teacher with 100% and a very good response from students with 98.6%. So conclution is the worksheet based on discovery learning was very feasible and very effective for use in 5th elementary school and received very good responses from students and teacher.